Pengungkapan Love Languange Dalam Hubungan Romantis - Putri Nainggolan; Qoni’ah Nur Wijayani (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Humans as social creatures interact to fulfill their needs in life. The need to be loved is one of the social needs that humans need. Therefore, humans always want to have a romantic relationship. A person can have a romantic relationship, which is also called dating. A boyfriend or girlfriend is an important need in a person's life because when they are with their partner a person is more courageous in expressing their ideas, thoughts, opinions, feelings and behavior, which makes it easier for them to be involved in the socialization process. Communication is the most important key in a relationship so that individuals understand each other and there are no misunderstandings between partners that result in the collapse of the relationship. Love language communication is the unique way each person expresses their affection in a relationship, which can be through words of affirmation, quality time, acts of service, receiving gifts, and physical touch. This theory was developed and introduced by Gary Chapman in 1992. This research employs a qualitative method, including interviews, document analysis, and field observations. The aim of this study is to discover the love languages of each individual in a relationship and how they express and communicate these love languages to their partners through everyday activities to satisfy their partners in maintaining a relationship. The research findings indicate that communication between couples in expressing their affection can vary, whether through verbal or non- verbal means, such as providing encouragement, spending quality time together, giving gifts, physical touch, and problem-solving using each partner's love language, discussing issues to find solutions to prevent prolonged conflicts.